2022
DOI: 10.3390/plants11050691
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nanomaterials on the Regulation of Gene Expression and Metabolomics of Plants under Salt Stress

Abstract: Plant salinity resistance results from a combination of responses at the physiological, molecular, cellular, and metabolic levels. This article focuses on plant stress tolerance mechanisms for controlling ion homeostasis, stress signaling, hormone metabolism, anti-oxidative enzymes, and osmotic balance after nanoparticle applications. Nanoparticles are used as an emerging tool to stimulate specific biochemical reactions related to plant ecophysiological output because of their small size, increased surface are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 178 publications
0
8
0
Order By: Relevance
“…Rich microbial flora can improve important soil characteristics such as soil structure, aggregation, compaction, pore spacing, and water penetration [36]. In addition, algae are a diverse group of mostly photosynthetic microorganisms that comprise both prokaryotic (cyanobacteria) and eukaryotic (green algae, euglenoids, and diatoms) species [37]. Algae can significantly raise soil fertility, which assists with plant development and protection by increasing nutrient availability [38], and provides an effective alternative to chemical fertilizers and pesticides in agricultural contexts, as well as producing bioactive chemicals such as phytohormones [39], developing root networking [40], and defending crops from plant pathogens and pests [40].…”
Section: Sustainable Solutions To Improve Soil Conditions and Plant H...mentioning
confidence: 99%
“…Rich microbial flora can improve important soil characteristics such as soil structure, aggregation, compaction, pore spacing, and water penetration [36]. In addition, algae are a diverse group of mostly photosynthetic microorganisms that comprise both prokaryotic (cyanobacteria) and eukaryotic (green algae, euglenoids, and diatoms) species [37]. Algae can significantly raise soil fertility, which assists with plant development and protection by increasing nutrient availability [38], and provides an effective alternative to chemical fertilizers and pesticides in agricultural contexts, as well as producing bioactive chemicals such as phytohormones [39], developing root networking [40], and defending crops from plant pathogens and pests [40].…”
Section: Sustainable Solutions To Improve Soil Conditions and Plant H...mentioning
confidence: 99%
“…However, little attention has been paid so far to the metabolic response of hydroprimed maize under salt stress in the early development stage. A systematic assessment of endogenous plant metabolites (metabolomics) can help unravel metabolic networks and shed light on interactions between plants and the environment ( Abideen et al., 2022 ). Roots are in close contact with the soil solution, they are first to confront excessive salinity and are the first places of “line of defence”.…”
Section: Introductionmentioning
confidence: 99%
“…Effect on Plant DNA and Gene Expression. It was shown that metal NPs can affect the level of expression of genes encoding the synthesis of the vacuolar proton exchanger, SOD, cytochrome P450-dependent oxidase, and PER, 153 miRNAs genes, 154 and genes encoding aquaporins in seeds. 155 Takehara et al 156 demonstrated that MgO NPs induce strong immunity against Fusarium wilt in tomatoes, which was associated also with differential expression of several genes and provided new insights into the probable genetic mechanisms explaining this immunity.…”
Section: Effect On Plant Resistance To Biotic Stresses and Phytopatho...mentioning
confidence: 99%